Iterative frequency-domain detection for IA-precoded MC-CDMA systems - Silva, Adão
Interference alignment (IA) is a promising technique that allows high capacity gains in interfering channels. On the other hand, iterative frequency-domain detection receivers based on the IB-DFE concept (Iterative Block Decision Feedback Equalization) can efficiently exploit the inherent space-frequency diversity of the MIMO MC-CDMA systems. In this paper we combine iterative IA precoding at the transmitter with IB-DFE based processing at the receiver for MC-CDMA systems. The receiver is designed in two steps: first a linear filter is used to mitigate the inter-user aligned interference, and then an iterative frequency-domain receiver is designed to efficiently separate the spatial streams in the presence of residual inter-user aligned interference at the output of the filter. The matrices for this non- linear space-frequency equalizer are obtained by minimizing the overall mean square error (MSE) of all data streams at each subcarrier. Our receiver structure is explicitly designed taking into account the residual inter-user interference, allowing both an efficient separation of the spatial streams and a reduction in the number of iterations of the IA procedure. We also propose a simple, yet accurate analytical approach for obtaining the performance of the proposed receiver structure. Our scheme achieves the maximum degrees of freedom provided by the IA precoding, while allowing an almost optimum space-diversity gain, with performance close to the matched filter bound (MFB).